Saccharum officinarum L. waste breakdown and the fertilizing effect on Raphanus sativus L. - Vélez-Lozano, Jorge; Burbano-Orjuela, Hernán; Navia, Jorge Fernando; Gómez, Eyder Daniel (Revista de Ciencias Agrícolas, 2019)
The agroindustry of the Panela generates a high pollutant load which is represented by liquids, gases and solids. Among the most polluting solid wastes, the sugarcane bagasse is the one that generates the most environmental impact because it is poured directly into the ravines, triggering serious conflicts in the social and economic order. The objective in this research was to obtain organic fertilizers, from the sugar cane residues, adding microbial broths which were enriched with fertilizers. Five treatments were evaluated. They included compost, microbial broth, nitrogen additions, phosphorus and a fully randomized control with three replicates. The physical and chemical variables were determined from the organic fertilizer, besides the fertilizer effect in Raphanus sativus L plants. The microbial broth application on the sugarcane bagasse allowed to obtain a good organic fertilizer content which was full of nitrogen, phosphorus, potassium, calcium and magnesium. From the enriched organic fertilizer application, in doses of 2 and 4 t/ha-1, a greater length of the aerial part of R. Sativus was obtained, which resulted in greater weight of the aerial part but also from the radical part.